Resistant Hypertension in Nondialysis Chronic Kidney Disease - Silvio Borrelli; Luca De Nicola; Giovanna Stanzione; Giuseppe Conte; Roberto Minutolo (International Journal of Hypertension)
Resistant hypertension (RH) is defined as blood pressure (BP) that remains above the target of less than 140/90 mmHg in the general population and 130/80 mmHg in people with diabetes mellitus or chronic kidney disease (CKD) in spite of the use of at least three full-dose antihypertensive drugs including a diuretic or as BP that reaches the target by means of four or more drugs. In CKD, RH is a common condition due to a combination of factors including sodium retention, increased activity of the renin-angiotensin system, and enhanced activity of the sympathetic nervous system. Before defining the hypertensive patient as resistant it is mandatory to exclude the so-called “pseudoresistance.” This condition, which refers to the apparent failure to reach BP target in spite of an appropriate antihypertensive treatment, is mainly caused by white coat hypertension that is prevalent (30%) in CKD patients. Recently we have demonstrated that “true” RH represents an independent risk factor for renal and cardiovascular outcomes in CKD patients.